Low rates of thiamine prescribing in adult patients with alcohol-related diagnoses in the emergency department. (2nd November 2021) - Peck, Nathan M.; Bania, Theodore C.; Chu, Jason
ABSTRACT: Background: Alcohol use disorder (AUD) is associated with thiamine deficiency and Wernicke-Korsakoff Syndrome (WKS). Thiamine supplementation for the prevention of WKS in patients with suspected AUD in the Emergency Department (ED) is generally recommended. As alcohol-related diagnoses are frequent reasons for visits to EDs, ED thiamine prescribing practices are relevant to the overall management and prevention of WKS in patients with AUD. Objective: To determine the prescription rates of thiamine to patients with alcohol-related diagnoses in the ED. Methods: This was a retrospective chart review conducted at two New York City urban teaching hospitals from January 1 to December 31, 2017. All patients 18 years or older who were given an alcohol-related diagnosis (all F10 ICD-10-CM codes) upon disposition were included. Collected data included details of thiamine prescribing practices, patient demographics and patient disposition. Results: A total of 7, 529 patient visits with an alcohol-related diagnosis were identified. The overall median age of included patients was 44; 5747 (76.3%) patient visits were by men; 310 (4.1%) patient visits resulted in admission. Out of all patient visits, thiamine was ordered during 167 (2.2%) visits, with thiamine administered parenterally during 129 (77.2%) visits and orally in 38 (22.8%) visits. Out of patient visits specifically associated with an F10.2 (Alcohol Dependence) diagnosis, thiamine was ordered during 105 (17.8%) visits. Conclusion: We found a very low rate of thiamine prescribing during patient visits associated with alcohol-related diagnoses. This may be a missed opportunity to reduce morbidity and mortality among AUD ED patients.